Anti-asthmatic activity of standardized hydro-ethanolic and aqueous extracts of Stachytarpheta cayennensis (Rich.) Vahl in a murine model. (10th February 2023) - Guimarães, Camila Carla; Sandy, Camila Mira; Figueira, Rebeca; Gonçalves, Mirani da Rocha; Crevelin, Eduardo José; Cardoso, Pedro Henrique; Fabro, Alexandre Todorovic; Carmona, Fabio; Borges, Marcos de Carvalho; Pereira, Ana Maria Soares
Abstract: Ethnopharmacological relevance: Stachytarpheta cayennensis (Verbenaceae) has been used in Brazilian traditional medicine to treat asthma and other respiratory diseases. Aims of the study: To investigate the effects of different doses of standardized hydro-ethanolic (SCH) and aqueous (SCA) extracts of aerial parts of S. cayennensis using a murine ovalbumin (OVA)-induced asthma model. Materials and methods: The major constituents of the plant extracts were identified and standardized by ultra-performance liquid chromatography coupled with mass spectrometry. Balb/c mice were challenged with OVA solution and treated concomitantly by intraperitoneal injection of standardized SCH or SCA extracts at 50, 100, and 200 mg/kg concentrations. OVA-challenged control animals were treated with either dexamethasone (OVA-DEX) or saline solution (OVA-SAL). After challenge, we assessed in vivo bronchial hyperresponsiveness, airway inflammation (number of cells), peribronchial inflammation (histological analysis) and production of OVA-specific IgE and interleukin (IL)-4, IL-5, and IL-13 (ELISA). Results: Acteoside, isoacteoside, and ipolamiide were the major constituents of SCH and SCA. The respective concentrations of acteoside in SCH and SCA were 78 and 98 μg/mL, while those of ipolamiide were 30 and 19 μg/mL. Treatment with 200 mg/kg of SCH or SCA decreased IL-4, IL-5, and IL-13 in lung homogenates. These reductions were accompanied by a lower influx of inflammatory cells (eosinophils, lymphocytes, and macrophages) to the airways and lungs. In addition to the anti-inflammatory effects, administration of SCA, but not SCH, ameliorated the parameters of bronchial hyperresponsiveness and decreased levels of circulating OVA-specific IgE. Conclusion: The results presented herein demonstrate for the first time the anti-asthmatic activity of S. cayennensis extracts in a murine model, thereby supporting the ethnopharmacological uses of the plant. Graphical abstract: Image 1